Effect of the Recreational Life Review Program on Patients with Dementia in an Outpatient Clinic: A Preliminary Study. Issue 3 (December 2014) - Li, Kuan-Yi; Hsu, Wen-Chuin; Lin, Li-Jung
The purpose of this study is to investigate the effect of the Life Review Program–Taiwan (LRP–TW) on outpatients with mild to moderate dementia. Ten individuals were selected through purposive sampling and tested using a single group pretest-posttest design. The Mini-Mental State Examination (MMSE), the Loewenstein Occupational Therapy Cognitive Assessment–Geriatric (LOTCA–G) and the Geriatric Depression Scale–Short Form (GDS–SF) were used as outcome measures. The total scores and three subtests of the LOTCA–G revealed significant differences after the intervention. Affective function remained stable through the experiment. The LRP–TW may offer a clinical intervention program for supporting cognitive and mental performance in individuals with dementia.